2017
DOI: 10.1038/s41551-017-0152-3
|View full text |Cite
|
Sign up to set email alerts
|

Non-destructive two-photon excited fluorescence imaging identifies early nodules in calcific aortic-valve disease

Abstract: Calcifications occur during the development of healthy bone, and at the onset of calcific aortic-valve disease (CAVD) and many other pathologies. Although the mechanisms regulating early calcium deposition are not fully understood, they may provide targets for new treatments and for early interventions. Here, we show that two-photon excited fluorescence (TPEF) can provide quantitative and sensitive readouts of calcific nodule formation, in particular in the context of CAVD. Specifically, by means of the decomp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 78 publications
1
37
0
Order By: Relevance
“…Previously, TPEF was used to monitor the progression of osteogenic differentiation in human mesenchymal stem cells (MSCs) 18,21,22 and ORR and mitochondrial FD was shown to correlate with the osteogenic differentiation of human MSCs 18 . Recently, TPEF imaging was utilized in vitro and on ex vivo tissue explants to detect mineralization, a key hallmark of CAVD 23 . In the context of VICs, we have previously shown that ORR correlated with cellular proliferative potential when VICs were cultured under different media conditions 24 .…”
mentioning
confidence: 99%
“…Previously, TPEF was used to monitor the progression of osteogenic differentiation in human mesenchymal stem cells (MSCs) 18,21,22 and ORR and mitochondrial FD was shown to correlate with the osteogenic differentiation of human MSCs 18 . Recently, TPEF imaging was utilized in vitro and on ex vivo tissue explants to detect mineralization, a key hallmark of CAVD 23 . In the context of VICs, we have previously shown that ORR correlated with cellular proliferative potential when VICs were cultured under different media conditions 24 .…”
mentioning
confidence: 99%
“…In this case, 2 alternative sets of filters are employed: 1 consisting of a filter FF01‐470/28 (Semrock Inc) and the other 1 of 2 filters—FF500‐Di01 and FF01‐510/84 (Semrock Inc)—placed in cascade. In fact, fluorescence signal was disaggregated in 2 spectral windows—one centered near to the emission maxima of collagen and elastin , the other for detecting fluorescence emission from smooth muscle cells and calcified tissues —in order to test (1) which band has the best discrimination capability and (2) if they provide complementary information to each other. Thus, Table summarizes the spectral ranges observed for each imaging modality.…”
Section: Methodsmentioning
confidence: 99%
“…Collagen emits a strong second-harmonic generation (SHG) signal due to its non-centrosymmetric structure with high second-order nonlinear susceptibility, while elastin, among different endogenous chromophores, such as keratin and melanin, can be visualized by another NLO technique, two-photon excitation fluorescence (TPF) [ 24 ]. In addition, TPF was found to be suitable for the detection of calcium depositions in artery walls and to track calcified nodule growth in aortic valves ex vivo [ 25 , 26 ]. In our present study, we visualized calcification and demonstrated the fragmentation of elastic fibers in the skin of PXE patients utilizing NLO microscopy imaging that allows the histologic diagnosis of the disease.…”
Section: Introductionmentioning
confidence: 99%